2012
DOI: 10.1371/journal.pone.0035567
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Telomere Length and Mortality in Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Some have suggested that chronic obstructive pulmonary disease (COPD) is a disease of accelerated aging. Aging is characterized by shortening of telomeres. The relationship of telomere length to important clinical outcomes such as mortality, disease progression and cancer in COPD is unknown. Using quantitative polymerase chain reaction (qPCR), we measured telomere length of peripheral leukocytes in 4,271 subjects with mild to moderate COPD who participated in the Lung Health Study (LHS). The subjects were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 25 publications
3
66
0
2
Order By: Relevance
“…Their length is affected by various factors, such as chronic inflammation or oxidative stress [3], but has also been shown to have a heritable component [12]. Recent data suggest that shorter telomere length is associated with an increased risk of total and cancer mortality in COPD patients [13]. Shortened telomeres were found in pulmonary vascular endothelial cells, alveolar epithelial cells and circulating leukocytes of COPD patients [14][15][16][17][18], supporting the notion of accelerated ageing in COPD.…”
Section: Introductionmentioning
confidence: 89%
“…Their length is affected by various factors, such as chronic inflammation or oxidative stress [3], but has also been shown to have a heritable component [12]. Recent data suggest that shorter telomere length is associated with an increased risk of total and cancer mortality in COPD patients [13]. Shortened telomeres were found in pulmonary vascular endothelial cells, alveolar epithelial cells and circulating leukocytes of COPD patients [14][15][16][17][18], supporting the notion of accelerated ageing in COPD.…”
Section: Introductionmentioning
confidence: 89%
“…A few studies have examined telomere length in populations of patients with COPD. They have consistently documented a reproducible shortening of telomere length in COPD, but the effect size was variable, and these studies did not examine extreme COPD phenotypes (42)(43)(44)(45). The recent discoveries indicate that telomere shortening, within certain abnormal thresholds relative to healthy populations, plays a causal role in mediating susceptibility.…”
Section: Implications For Diagnostic and Patient Care Decisionsmentioning
confidence: 99%
“…Mutations that decrease telomerase and cause short telomeres in humans lead to a spectrum of premature-onset diseases and conditions collectively termed "telomere syndromes," which share many features of the common diseases of aging in the human population (Armanios and Blackburn 2012). Multiple independent studies have found impaired human telomeric DNA length maintenance to be associated with a wide range of diseases and for several age-related diseases to predict future risks and outcomes including mortality (Von Zglinicki et al 2000;Samani et al 2001;Cawthon et al 2003;Panossian et al 2003;Valdes et al 2005;Bischoff et al 2006;Harris et al 2006;MartinRuiz et al 2006;Bakaysa et al 2007;Brouilette et al 2007;Fitzpatrick et al 2007Fitzpatrick et al , 2011Aubert and Lansdorp 2008;Farzaneh-Far et al 2008;Kimura et al 2008;Epel et al 2009;Njajou et al 2009;Astrup et al 2010;Codd et al 2010Codd et al , 2013Salpea et al 2010;Willeit et al 2010a,b;Zee et al 2010;Strandberg et al 2011;Wentzensen et al 2011;Yaffe et al 2011;Honig et al 2012;Lee et al 2012;Weischer et al 2012;Bojesen 2013;Muezzinler et al 2013;Gardner et al 2014;Haycock et al 2014;Walsh et al 2014).…”
mentioning
confidence: 99%
“…A recent study incorporating data from the National Health and Nutrition Examination Survey (NHANES) 1999-2002, a large, nationally representative, ethnically and socioeconomically diverse sample, reported that sex, race-ethnicity, and socioeconomic status (SES) moderated the associations between TL and mortality in older individuals (Needham et al 2012). However, while some human cohort studies have found shorter PBMC TL or LTL is associated with increased mortality (Cawthon et al 2003;Martin-Ruiz et al 2006;Bakaysa et al 2007;Farzaneh-Far et al 2008;Kimura et al 2008;Epel et al 2009;Astrup et al 2010;Willeit et al 2010b;Fitzpatrick et al 2011;Honig et al 2012;Lee et al 2012;Weischer et al 2012), others have not (Bischoff et al 2006;Harris et al 2006;Njajou et al 2009;Strandberg et al 2011). These inconsistencies in the literature may be due to differences in study cohorts, sample sizes, assay methods, and other methodological differences (Bojesen 2013).…”
mentioning
confidence: 99%